2007
DOI: 10.1128/aem.02250-06
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Ecological Control of Geosmin and 2-Methylisoborneol in Source Waters

Abstract: 2The majority of all biologically caused taste-and-odor outbreaks in drinking water characterized worldwide are caused by microbial production of (Ϫ)-geosmin [(Ϫ)-(4S,4aS,8aR)-4,8a-dimethyloctahydronaphthalen-4a-ol] and (Ϫ)-2-methylisoborneol (2-MIB) {(1R-exo)-1,2,7,7-tetramethylbicyclo[2.2.1]heptan-2-ol}. Since they were first identified in the early 1960s, these two earthy-muddy-smelling metabolites have been the focus of considerable research, which has collectively produced over 400 scientific articles, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
262
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(289 citation statements)
references
References 107 publications
8
262
2
9
Order By: Relevance
“…Similarly, Dzialowski et al (2009) found that cyanobacterial biovolume is not a consistent predictor of dissolved geosmin, and Durrerl et al (1999) indicated that correlations between a particular taxon and particle-bound geosmin cannot be expected to occur in any instance in natural waters. On the contrary, a few researchers observed positive correlation between geosmin and cyanobacterial biovolume (Jüttner and Watson, 2007;Sugiura et al, 2004). Li et al (2007) suggested that dissolved odorous compounds are affected by various factors, such as rate of odor production by algal cells, biodegradation by microbes, photolysis by sunlight, absorption by particles, disturbance by wave and volatilisation of odorous compounds themselves.…”
Section: Algal Biomass and MC Concentrationmentioning
confidence: 99%
“…Similarly, Dzialowski et al (2009) found that cyanobacterial biovolume is not a consistent predictor of dissolved geosmin, and Durrerl et al (1999) indicated that correlations between a particular taxon and particle-bound geosmin cannot be expected to occur in any instance in natural waters. On the contrary, a few researchers observed positive correlation between geosmin and cyanobacterial biovolume (Jüttner and Watson, 2007;Sugiura et al, 2004). Li et al (2007) suggested that dissolved odorous compounds are affected by various factors, such as rate of odor production by algal cells, biodegradation by microbes, photolysis by sunlight, absorption by particles, disturbance by wave and volatilisation of odorous compounds themselves.…”
Section: Algal Biomass and MC Concentrationmentioning
confidence: 99%
“…There have been numerous studies on odorous compounds in drinking water, water products, and the surface waters of lakes, reservoirs and rivers; however, few of these studies have investigated geosmin and 2-MIB in the benthic environment or in the surrounded biofilms and investigated the effect of the benthic production of these compounds on water bodies and water products (Jü ttner and Watson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Three strains of T. bourrellyi isolated from Lake Erhai were shown to produce both β-ionone and geosmin in the present study. Although no direct evidence demonstrated the health risks of geosmin and MIB for humans or aquatic animals (Dionigi et al 1993;Jüttner and Watson 2007), these two mustyearthy monoterpene and sesquiterpene metabolites have been regarded as the cause of frequent taste and odor incidents in water supplies, because of their strong earthy smell and extraordinarily low sensory threshold as 2-20 ng L −1 for humans (Cook et al 2001;Izaguirre and Taylor 2004). Therefore, the presence of T. bourrellyi, the geosmin producer, implied a potential off-flavor risk for water quality around Lake Erhai.…”
Section: Discussionmentioning
confidence: 99%
“…This species was reported to form exceptional Oscillatoria-like blooms (Revaclier 1978;Berglind et al 1983;Ganf et al 1991). Furthermore, Responsible editor: Philippe Garrigues T. bourrellyi also produces geosmin or β-ionone (Berglind et al 1983;Jüttner and Watson 2007;Shao et al 2013), exhibiting potential harmful impact. T. bourrellyi is one of the three formally accepted species of the genus Tychonema in the latest edition of Oscillatoriales taxonomy by Komárek and Anagnostidis (2005).…”
Section: Introductionmentioning
confidence: 99%